Wild boar carcasses in the center of boar activity: crucial risks of ASF transmission - Cukor, Jan; Faltusová, Monika; Vacek, Zdeněk; Linda, Rostislav; Skoták, Vlastimil; Václavek, Petr; Ježek, Miloš; Šálek, Martin; Havránek, František (Frontiers in Veterinary Science, 2024)
African swine fever (ASF) is a highly virulent disease rapidly spreading through Europe with fatal consequences for wild boar and domestic pigs. Understanding pathogen transmission among individuals and populations is crucial for disease control. However, the carcass attractiveness for boars was surprisingly almost unstudied. Here, we evaluated if the wild boar carcasses are perceived as an attractant compared to the control sites throughout the year. For this purpose, 28 wild boar carcasses were placed in seven forest stands and continuously monitored in 2019–2020 by camera traps combined with control locations situated at least 200 m away in comparable habitats. Overall, we have recorded 3,602 wild boar visits, from which 3,017 (83.8%) were recorded in locations with placed carcasses and 585 (16.2%) in control locations. Most visits were recorded after sunset and before sunrise, corresponding to common peaks of wild boar activity. On average, the first visits were detected 4.7 days after carcass placement. Contrarily, it was 61.5 days for the control site. In conclusion, we have proven an enormous wild boar carcass attractiveness for boars, which exhibits an entirely new aspect of wild boar behavior. Therefore, the carcass removal is a crucial measure for controlling the spread of ASF.